POSITIVE EFFECTS OF CULTIVATION TECHNOLOGIES BASED ON GEOREFERENCED DATA ON THE ECONOMIC SUSTAINABILITY OF WINTER WHEAT PRODUCTION - Szabo, Levente; Szabó, Emese; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2023)
Elements of precision farming, such as auto-steer navigation, section control and variable rate application, can have a positive impact on farming performance, yet the uptake of these technologies has been slow and farmers are not convinced that they can achieve ad- ditional benefits by switching to them. Therefore, the authors considered it important to examine the impact of precision farming on winter wheat yields based on data from Hungarian farms. Yield data from farms with a yield map in the MyJohnDeere database from 2018-2022 and yield and cost data from 48 farms with Variable Rate Application (VRA) from 2018-2022 were evaluated and compared to the national average. MyJohnDeere and VRA farms had significantly higher yields in all years. Despite the cost saving from the introduction of precision farming, such as non-overlapping input application, the total costs of the examined VRA farms were higher, which can be explained by more intensive production beyond precision farming. It can also be argued that the additional inputs of the VRA farms were outweighed by the additional production value, with their specific incomes being higher than the national average in all years. In conclusion, the profitability of winter wheat production - and thus its resilience to a changing economic environment - can be increased at farm scale by adapting preci- sion farming. Technological change by farmers, in particular the widespread adoption of variable rate application, could also increase the sustainability of winter wheat production at the farm scale.